Blended Learning Impacts on Higher Education: What Have Research Revealed? - Umi Kalsom, Masrom; Nik Aloesnita, Nik Mohd Alwi (Penerbit Unisza, 2021)
The application of technology in teaching and learning process has caught great attention from instructors and practitioners around the world including those at Higher Education Institutions (HEis) in Malaysia.